STUDI KOMUNITAS MAKROZOOBENTOS DI HUTAN MANGROVE KECAMATAN INSANA UTARA KABUPATEN TIMOR TENGAH UTARA - Ludgardis Ledheng; Yolanda Getrudis Naisumu (Politeknik Pertanian Negeri Kupang, 2018)
The development in Wini Beach coastal area will have an impact on the destruction of the mangrove ecosystem which is a habitat for the life of the macrozoobenthic fauna. This study aims to determine the community structure of macrozoobenthos including abundance, diversity, evenness and dominance of the type of macrozoobenthos in the mangrove area. The study was carried out in the District of North Insana which included the mangrove area of Temkuna Beach (station I) and the mangrove area of Tanjung Bastian Beach (station II). Taking macrozoobenthos samples was carried out at low tide using the line transect method which was made perpendicular to the land in the mangrove forest area. The results of the study found 13 types of macrozoobenthos fauna spread over 2 stations namely the 8-type gastropod class, bivalvia class 4 types and 1 type crustacean class. Medium category (H ') = 2.41 index, Uniformity Index (E) = 0.938 classified as stable community and Dominance index (D) = 0.10 low category. The Equity Index score is classified as a stable conditionwhere no macrozoobenthos species dominate. Virtual sex chat with porn models on webcam. Moscow and the world! Hundreds of guys and girls online. Start chatting now! Come in live cam girl naked free-naked scared, pussy get pictures with the inscription, mom wants more porn. Watch porn video chat with naked girls you can without registration, enjoy free erotic sex show in real time.